A SWOT Analysis on Jasmine Used Book Store in Taiwan (Journal of Business Management and Accounting, 2016)
The objective of this study is to perform a SWOT analysis on a used bookstore in Taiwan named Jasmine. Semi-structured interviews, observations and documents review were used for data collection. Jasmine used bookstore aims for better sales and higher profits  besides  promoting  a  reading  culture  among  the  Taiwanese  society  through charitable activities. Employee hiring and training process are important to Jasmine’s top management in order to ensure customer satisfaction. Inventory management, independent business model and employee’s satisfaction/retention are acknowledged to be Jasmine’s weaknesses. As for opportunities and threats, external threats from globalization and e-books transformation are foreseeable for a used book store like Jasmine albeit having a supportive government and strong reading culture among the Taiwanese society. This paper intends to provide an up-close and in depth examination of SWOT analysis based on a real case perspective.